PATIENT SATISFACTION SURVEYS AND QUALITY OF CARE: AN INFORMATION PAPER OF BAZNAS FREE HOSPITAL, INDONESIA - Muhammad Hasbi Zaenal; Muhammad Choirin; Ayu Sholihah Sadariyah; Amelya Dwi Astuti (International Journal of Accounting, Finance and Business, 2019)
Abstract: The purpose of this paper is to investigate the patient satisfaction surveys and quality of care BAZNAS free hospital development. The hospital built through the waqf and zakat integration scheme. In Islam, zakat and waqf are decidedly in Maqasid al-Shari'ah concept to overcome the poverty problem and fulfillment the basic needs. The joint elements are needed to obtain the highest utility as part of the social obligations which can contribute to improving the quality of life. The paper will demonstrate that zakat and waqf integration plays an essential role in providing a better life for the poor. The surveys conducted on May-July 2017 by the 400 patients in four different branches (Jakarta, Makassar, Sidoarjo and Pangkalpinang). This paper founds that zakat, and waqf integration has brought benefits for the poor as well the quality of life among them can be further enhanced. BAZNAS Free Hospitals has proven to play a vital role in the Sustainable Development Goals (SDG's) related to global health and well-being.